Comparison of the impact of two interdental cleaning devices on the reduction of bleeding around implants - Monica J Mahajani; Molly Kalla; Subhash Sonkesriya; Parth Mehra; Rashmi Laddha; Grusha Akade (Wolters Kluwer Medknow Publications, 2024)
Objective: Purpose: To evaluate the efficacy of water flossing to traditional flossing in lowering the bleeding on probing (BOP) index around dental implants. Methods and Materials: This single-center, examiner-masked research enrolled patients with implants and randomly allocated them to one of two groups. The research analyzed the effectiveness of manual toothbrushes when used with either string floss or a water flosser. Results: After 30 days, the main result was a decrease in BOP occurrence. At the outset, neither group had noticeably higher rates of bleeding than the other. While only six of 20 implants in the floss group demonstrated a decrease in BOP after 30 days, 18 of 20 implants in the water flosser group did. Conclusions: These results demonstrate that the use of water flossers was associated with much less bleeding than that of string floss. The researchers think that water flossing might be a useful addition to the maintenance of dental implants.